Selyamet Gerai Gazebo in Bakhchisarai Palace Complex - Lomakin Dmitry A.; Aibabina Elena A. (Археология евразийских степей, 2022)
The plans of the Bakhchisarai Khan Palace of the 18th–20th centuries (G. Trombaro, W. Hastie, N. P. Krasnov, A. L. Rotach) feature an ‘Old Palace’ of the Crimean khans, probably built in the 16th century under Khan Sahib I Gerai (reigned in 1532–1551), and later sources only refer to a surviving gallery. Throughout its existence, the palace was guarded by the khans and was invariably restored after the destruction, being one of the first structures in the territory of the palace complex, serving as a symbol of Khan's power associated with the birth of the new capital – Bakhchisaray. In the 1820s the ‘Old Palace’ was dismantled as a completely dilapidated structure, but the restorers preserved its gallery, which was later named the Selyamet Gerai Gazebo. The gazebo with a fountain in the center of the room, which stood on a high basement, with a marble colonnade and arched openings of a lancet shape, was decorated with stucco decor and painting in naturalistic and baroque style, which was included in the art and craft of Turkey and the Crimean Khanate in the second half of the 16th–18th centuries. The gazebo was destroyed in the middle of the 20th century.